Hepatitis C disease severity in living versus deceased donor liver transplant recipients: An extended observation study. Issue 4 (1st March 2014) - Terrault, Norah A.; Stravitz, R. Todd; Lok, Anna S.F.; Everson, Greg T.; Brown, Robert S.; Kulik, Laura M.; Olthoff, Kim M.; Saab, Sammy; Adeyi, Ovedele; Argo, Curtis K.; Everhart, Jay E.; Rodrigo, Del R.; et al.
<x xml:space="preserve">Abstract</x> Donor factors influence hepatitis C virus (HCV) disease severity in liver transplant (LT) recipients. Living donors, because they are typically young and have short cold ischemic times, may be advantageous for HCV‐infected patients. Among HCV‐infected patients in the Adult‐to‐Adult Living Donor Liver Transplantation Cohort Study (A2ALL) surviving >90 days and followed for a median 4.7 years, advanced fibrosis (Ishak stage ≥3) and graft loss were determined. The 5‐year cumulative risk of advanced fibrosis was 44% and 37% in living donor LT (LDLT) and deceased donor LT (DDLT) patients (P = 0.16), respectively. Aspartate aminotransferase (AST) activity at LT (hazard ratio [HR] = 1.38 for doubling of AST, P = 0.005) and biliary strictures (HR = 2.68, P = 0.0001) were associated with advanced fibrosis, but LDLT was not (HR = 1.11, 95% confidence interval [CI] 0.73‐1.69, P = 0.63). The 5‐year unadjusted patient and graft survival probabilities were 79% and 78% in LDLT, and 77% and 75% in DDLT (P = 0.43 and 0.32), with 27% and 20% of LDLT and DDLT graft losses due to HCV (P = 0.45). Biliary strictures (HR = 2.25, P = 0.0006), creatinine at LT (HR = 1.74 for doubling of creatinine, P = 0.0004), and AST at LT (HR = 1.36 for doubling of AST, P = 0.004) were associated with graft loss, but LDLT was not (HR = 0.76, 95% CI: 0.49‐1.18, P = 0.23). Conclusion: Donor type does not affect the probability of advanced fibrosis or patient and graft survival in HCV‐infected recipients. Thus, while LDLT offers the advantage of shorter wait times, there is no apparent benefit for HCV disease progression. Biliary strictures have a negative effect on HCV fibrosis severity and graft survival, and a high AST at LT may be an important predictor of fibrosis risk post‐LT. (Hepatology 2014;59:1311‐1319)